2004
DOI: 10.1177/108471380400800102
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Cochlear Implants

Abstract: More than 60,000 people worldwide use cochlear implants as a means to restore functional hearing. Although individual performance variability is still high, an average implant user can talk on the phone in a quiet environment. Cochlear-implant research has also matured as a field, as evidenced by the exponential growth in both the patient population and scientific publication. The present report examines current issues related to audiologic, clinical, engineering, anatomic, and physiologic aspects of cochlear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
238
0
6

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 329 publications
(256 citation statements)
references
References 148 publications
3
238
0
6
Order By: Relevance
“…These electrodes were developed on a micropatterned polyimide substrate, which was chosen because of its biocompatibility, flexibility and structural properties [27]. The structure (shown in Figure 3) is double sided and has eight evenly spaced recording sites with four sites per side.…”
Section: B Thin-film Lifesmentioning
confidence: 99%
“…These electrodes were developed on a micropatterned polyimide substrate, which was chosen because of its biocompatibility, flexibility and structural properties [27]. The structure (shown in Figure 3) is double sided and has eight evenly spaced recording sites with four sites per side.…”
Section: B Thin-film Lifesmentioning
confidence: 99%
“…The use of qualitative general stimuli such as brushing and stroking, instead of focusing on stimuli to quantitatively characterize single unit responses, was an attempt to generate a more natural data set of responses. The problem is well known in the field of cochlear implants where in early days a single-electrode cochlear implant could only provide some closed-set speech recognition with no open-set recognition at all while now modern devices can provide 70-80% open-set speech recognition (Zeng, 2004).…”
Section: Open Issuesmentioning
confidence: 99%
“…Although speech recognition is remarkably good in most patients with cochlear implants, with average sentence recognition ≥ 80% correct in quiet (see Zeng, 2004 for a review), reduced speech recognition in noise is one of the major problems faced by most implant users. Skinner et al (2002) reported that one third of the 62 postlingually-deafened cochlear implant users tested at a fairly moderate +10 dB signal-to-noise ratio scored below 75% correct in sentence recognition.…”
Section: Introductionmentioning
confidence: 99%